غالب کا دارالسرور - Ali, Dr. Liaquat (Zoraiz, 2022)
Ghalib is a legend Urdu poet. He was brought up in a well off family. He had passion against the services of his guardian uncle, from the East India Company. During the anarchy of 1857, he was deprived of the pension. So he had to contact Yousaf Ali Nazim (Nawwab of Ram Pur, Ghalib’s student during his stay at Dehli). Ghalib visited Rampur twice in his life. He was impressed by the weather and landscape of Ram Pur. He called it Dar us Suroor, admiring in a verse. A stipend of Rs. 100 was sanctioned for him by the state. His Relationship with the ruler was personal as well as political because he used to inform day to day circumstances to the Nawwab. Some Poets mentioned in this article were formal students of Ghalib at Ram Pur.